Assessment of right ventricle volumes and function by cardiac MRI: Quantification of the regional and global interobserver variability - Bonnemains, Laurent; Mandry, Damien; Marie, Pierre-Yves; Micard, Emilien; Chen, Bailiang; Vuissoz, Pierre-André (Magnetic resonance in medicine, 2012)
Reproducibility of the manual assessment of right ventricle volumes by short‐axis cine‐MRI remains low and is often attributed to the difficulty in separating the right atrium from the ventricle. This study was designed to evaluate the regional interobserver variability of the right ventricle volume assessment to identify segmentation zones with the highest interobserver variability. Short‐axis views of 90 right ventricles (30 hypertrophic, 30 dilated, and 30 normal) were acquired with 2D steady‐state free precession sequences at 1.5 T and were manually segmented by two observers. The two segmentations were compared and the variations were quantified with a variation score based on the Hausdorff distance between the two segmentations and the interobserver 95% limits of concordance of the global volumes. The right ventricles were semiautomatically split into four subregions: apex, mid‐ventricle, tricuspid zone, and infundibulum. These four subregions represented 11%, 34%, 36%, and 19% of the volume but, respectively, yielded variation scores of 8%, 16%, 42%, and 34%. The infundibulum yielded the highest interobserver regional variability although its variation score remained comparable to the tricuspid zone due to its lower volume. These results emphasize the importance of standardizing the segmentation of the infundibulum and the tricuspid zone to improve reproducibility. Magn Reson Med, 2011. © 2011 Wiley‐Liss, Inc.